Reconstruction of the Basis and Objectives of the Islamic Religious Education Curriculum in the Era of Digital Transformation - Riska Febriani; Maulidnear Doa Salsabil; Sumiarti Sumiarti; Rafiqa Noviyani (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
The reconstruction of the Islamic Religious Education (PAI) curriculum is a process of developing the curriculum to align with digital transformation while maintaining Islamic values. This article aims to discuss the foundations and objectives of the PAI curriculum in the digital transformation era. The study employs a qualitative approach through library research. Data were collected from various scientific references and analyzed using content analysis techniques. The findings indicate that the development of the PAI curriculum should be based on religious, philosophical, psychological, sociological, and technological aspects. In addition, the PAI curriculum is also directed toward improving students’ digital literacy and critical thinking skills.